A density functional theory based analysis of photoinduced electron transfer in a triazacryptand based K+ sensor - Briggs, Edward A.; Besley, Nicholas A. (American Chemical Society, 2015)
The electronic structure and photoinduced electron transfer processes in a K+ fluorescent sensor that comprises a 4-amino-naphthalimide derived fluorophore with a triazacryptand lig- and is investigated using density functional theory (DFT) and time-dependent density functional theory (TDDFT) in order to rationalise the function of the sensor. The absorption and emission energies of the intense electronic excitation localised on the fluorophore are accurately described using a ∆SCF Kohn-Sham DFT approach, which gives excitation energies closer to experiment than TDDFT. Analysis of the molecular orbital diagram arising from DFT calculations for the isolated molecule or with implicit solvent cannot account for the function of the sensor and it is necessary to consider the relative energies of the electronic states formed from the local excitation on the fluorophore and the lowest fluorophore→chelator charge transfer state. The inclusion of solvent in these calculations is critical since the strong interaction of the charge transfer state with the solvent lowers it energy below the local fluorophore excited state making a reductive photoinduced electron transfer possible in the absence of K+, while no such process is possible when the sensor is bound to K+. The rate of electron transfer is quantified using Marcus theory, which gives a rate of electron transfer of k_ET=5.98 x 10^6 s−1.